Happiness at work: Gen Z’s experience in finding meaning in their work - Bertha Kristiyanti; Ika Febrian Kristiana (Personifikasi: Jurnal Ilmu Psikologi, 2026)
Indonesia is one of the countries that employs Gen Z on a large scale. It is known that the industry turnover rate in Indonesia reaches above 10% on average. Generation Z is known to be the most unhappy generation; they expressed feeling unhappy with their jobs for 22% of their time. The question in this study is to explore how Gen Z experiences in making meaning of their work. A descriptive phenomenological qualitative research design was chosen to get a picture of the experience of finding the meaning of work for Gen Z. The participants involved in this study amounted to three people, with the characteristics of participants being Gen Z and having a minimum tenure of three years. The participants consisted of two women and one man, who was 26 years old and worked as an employee. Data were collected through in-depth interviews online and face-to-face. The results of this study show that there are things that influence finding happiness at work, namely career decision making, success in adjusting, compatibility with the work done, and support from coworkers. Participants mentioned that the fit with the work they do and the support of coworkers have a big influence on their finding happiness at work. For future research, more in-depth research can be conducted on other psychological aspects in the industrial field, as well as research using quantitative methods to examine the variable of employee happiness at work in relation to several other variables, involving a larger number of subjects.